Mainstreaming gender into National Adaptation Planning and implementation in Sub-Saharan Africa - Chingarande, Dominica; Huyer, Sophia; Lanzarini, Silvia; Makokha, Jackline N; Masiko, Winifred K; Mungai, Catherine; Njuki, Jemimah; Adera, Edith Ofwona; Omolo, Nancy; Wamukoya, George; Waroga, Valentine (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Climate change adaptation is dependent on access to a number of resources, including information, land, financing, and mobility. Successful climate change adaptation, therefore, will need to integrate an understanding of gender and take action on it, including an appreciation for the importance of women in climate change mitigation and adaptation strategies. This paper undertakes a review of the policies and legal frameworks for gender and climate change, including key UNFCCC decisions on gender and climate change and gender mainstreaming in National Adaptation Planning process. An analysis of resiliency is also included by examining gender inequalities in the ownership, access, and control over natural resources, and seeking to understand how gender inequalities shape, and are shaped by, priorities, experiences, and adaptive capacity in the wake of system shocks. The paper also provides examples of best practices at the policy, institutional, and programme level as well as throughout planning processes.